3D bioprinting : modeling in vitro tissues and organs using tissue-specific bioinks /: modeling in vitro tissues and organs using tissue-specific bioinks. ([2019]) - Cho, Dong Woo; Kim, Byoung Soo; Jang, Jinah; Gao, Ge; Han, Wonil; Singh, Narendra K
No abstract available